Country of Origin, Brand Image, and Customer Loyalty: The Investigation of Users of Skincare Products - Nur, Nur; Mariana, Ana; Santi, Septhani Santi (Dinasti Publisher, 2026)
This study examines the impact of country of origin (COO) and brand image (BI) on customer loyalty (CL), and the influence of COO on BI. Using survey data collected between March and April 2024 and a covariance-based structural equation model, this study confirms three positive relationships, as supported by the goodness-of-fit indices. The higher the COO and the BI, the higher the CL, and the higher the COO, the higher the BI. Practically, this study suggests that manufacturers of local and foreign skincare products prioritize creating a brand image that fosters consumer loyalty by focusing on producing safe products for consumers, and the company hiring influencers must inform them with the necessary knowledge and benefits, supported by their testimony after using the skincare products freely given in advance.